IMPLEMENTASI PROGRAM TEMPAT OLAH SAMPAH SETEMPAT (TOSS) DALAM MENUNJANG INDUSTRI EKONOMI KREATIF GUNA PEMENUHAN KEBUTUHAN LISTRIK DI KABUPATEN KLUNGKUNG - Baykhaqi, Elmi Achmad; Yasintha, Putu Nomy; Winaya, I Ketut (CITIZEN CHARTER, 2020)
wastes and has not manage properly, the Klungkung Regency Government has made an innovation as the handling and management of waste based on reduce, reuse, and recycle. Te purpose of this study is analyzing about how the excecution of Local Waste Management Innovation that support industries in term of electricity in Klungkung Regency. This study uses descriptive qualitative research method, and also it was examined based on Merrille S. Grindle’s concept, the policy implementation model. This research has result that the TOSS program has been quite successfully implemented but it has not been maximum based on implementation of the program indicator cause still found the technical problems that directly related to operational. Keywords: Waste Management, Implementation, Industries